Introduction au dossier « Citoyen, cité, espace et communautés sous l'Ancien Régime » - Claire Dolan (Les Cahiers de Framespa)
School, citizenship, as well as relationships between citizens and governments today, in France and in the Province of Quebec, are themes which were discussed at a conference the main topic of which was Old Regime France. Citizen, city, space, and communities were dealt with in papers which are presented here.